2020
DOI: 10.1101/2020.12.14.422631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

deepBlink: Threshold-independent detection and localization of diffraction-limited spots

Abstract: Detection of diffraction-limited spots is traditionally performed with mathematical operators designed for idealized spots. This process requires manual tuning of parameters that is time-consuming and not always reliable. We have developed deepBlink, a neural network- based method to detect and localize spots automatically and demonstrate that deepBlink outperforms state-of-the-art methods across six publicly available datasets. deepBlink is open-sourced on PyPI and GitHub (https://github.com/BBQuercus/deepBli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…To complete the comparison, we applied our M hybrid model to the smFISH test dataset DS dB made available with the deepBlink publication and containing 129 smFISH images. The results reported for the prediction of M dB for the DS dB dataset is the result obtained by the authors and reported in (Eichenberger et al, 2021). Not surprisingly, deepBlink model performance is better on their own smFISH images, however DeepSpot managed to have an F1-score of nearly 88%, a noticeable achievement since the model has not been trained on the DS dB data.…”
Section: Deepspot Enables More Accurate Spot Detection Compared With Deep-blinksupporting
confidence: 61%
See 2 more Smart Citations
“…To complete the comparison, we applied our M hybrid model to the smFISH test dataset DS dB made available with the deepBlink publication and containing 129 smFISH images. The results reported for the prediction of M dB for the DS dB dataset is the result obtained by the authors and reported in (Eichenberger et al, 2021). Not surprisingly, deepBlink model performance is better on their own smFISH images, however DeepSpot managed to have an F1-score of nearly 88%, a noticeable achievement since the model has not been trained on the DS dB data.…”
Section: Deepspot Enables More Accurate Spot Detection Compared With Deep-blinksupporting
confidence: 61%
“…Deep-learning networks have been introduced for mRNA spot detection (Gudla et al, 2017; Mabaso et al, 2018), and more recently deepBlink (Eichenberger et al, 2021). The latter focuses on a fully convolutional neural network based on the U-Net architecture.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…RS-FISH performance was benchmarked against the leading tools for single-molecule spot detection in images. The tools compared in the benchmarking are FISH-quant 14 (Matlab), Big-FISH 26 (Python), AIRLOCALIZE 17 (Matlab), Starfish 16 (Python), and deepBlink 15 (Python, TensorFlow). Localization performance comparison was done on simulated images with known ground truth spot locations, and computation time comparison was performed using real three-dimensional C. elegans smFISH images.…”
Section: Methodsmentioning
confidence: 99%
“…To validate and benchmark RS-FISH, we performed quantitative comparisons against FISH-quant 14 , Big-FISH 26 , AIRLOCALIZE 17 , Starfish 16 , and deepBlink 15 using (i) simulated smFISH images with varying noise levels to assess detection performance, (ii) real C. elegans embryo datasets for runtime measurements, and (iii) large lightsheet datasets 13 . We show that RS-FISH is on par with the best methods in terms of detection performance ( Fig.…”
Section: Mainmentioning
confidence: 99%